Evalu-light: A practical approach for evaluating character lighting in real-time - Mc Donnell, Rachel (My University, 2020)
The demand for cartoon animation content is on the rise, driven largely by social media, video conferencing and virtual reality. New content creation tools and the availability of open-source game engines allow characters to be animated by even novice creators (e.g., Loomie and Pinscreen for creating characters, Hyprface and MotionX for facial motion capture, etc,). However, lighting of animated characters is a skilled art-form, and there is a lack of guidelines for lighting characters expressing emotion in an appealing manner. Recent perceptual research has attempted to provide user guidelines through rigorous and labor-intensive rating-scale experiments exploring many parameters of light [Wisessing et al. 2016, 2020]. We propose an alternative approach based on the method of adjustment, similar to common lighting tools in 3D content creation software, but with the power of modern real-time graphics. Our framework allows users to interactively adjust lighting parameters and instantly assess the results on the animated characters, instead of having to wait for the render to complete.
Proceedings - SAP 2020: ACM Symposium on Applied Perception
PUBLISHED
Keywords: cartoon animation; open-source game engines; user guidelines; Character lighting; Virtual characters; Evaluation; Emotion; Appeal